Community Forestry Governance: Lessons for Cameroon and Nepal. Issue 4 (3rd April 2022) - Kimengsi, Jude Ndzifon; Bhusal, Prabin
Abstract: Community forestry (CF) signaled the institution of governance mechanisms for forest management and community livelihoods. Till date, there is still a strong debate on the outcomes linked to CF governance. Scholars agree on the need for shared-learning in advancing CF in the Global South. We contribute here, by comparatively reviewing CF governance processes and outcomes for two regional pacesetters – Cameroon and Nepal. Guided by the Program on Forests (PROFOR) framework, we review 60 articles and 12 institutional reports, and discuss what both countries can (un)learn. We derive five key lessons: (1) As in Nepal, Cameroon needs a strong legal and institutional setup. (2) Multiple legal entities complicate CF governance in terms of peasants' membership inclusion. (3) Cameroon's policy reforms can draw inspiration from Nepal to ensure significant female representation. (4) Instituting scientific forestry does not necessarily usher in benefits to peasant households. (5) Both countries need reforms to overcome techno-oriented CF approaches.